2019
DOI: 10.1111/desc.12842
|View full text |Cite
|
Sign up to set email alerts
|

Children, but not great apes, respect ownership

Abstract: Access to and control of resources is a major source of costly conflicts. Animals, under some conditions, respect what others control and use (i.e. possession). Humans not only respect possession of resources, they also respect ownership. Ownership can be viewed as a cooperative arrangement, where individuals inhibit their tendency to take others’ property on the condition that those others will do the same. We investigated to what degree great apes follow this principle, as compared to human children. We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…As another example, Schaefer et al (2015) found that 4- to 11-year-old children from three different cultural groups (one WEIRD – Western, educated, industrialized, rich, and democratic – and two small-scale African cultures) took into account work-based merit (i.e., based on who produces the most resources) in culturally specific ways (some giving it more weight than others) when deciding how to divvy up collaboratively acquired resources. And Kanngeisser et al (2019) found that while children from several very different cultural contexts all respected the property of others, there was at the same time cultural variation in how much they did so.…”
Section: A Shared Intentionality Accountmentioning
confidence: 99%
“…As another example, Schaefer et al (2015) found that 4- to 11-year-old children from three different cultural groups (one WEIRD – Western, educated, industrialized, rich, and democratic – and two small-scale African cultures) took into account work-based merit (i.e., based on who produces the most resources) in culturally specific ways (some giving it more weight than others) when deciding how to divvy up collaboratively acquired resources. And Kanngeisser et al (2019) found that while children from several very different cultural contexts all respected the property of others, there was at the same time cultural variation in how much they did so.…”
Section: A Shared Intentionality Accountmentioning
confidence: 99%
“…Today, the concept of ownership is present in nearly all existing human languages and cultures, and it has been shown to emerge early in childhood ( Boyer, 2015 ). Two-year-olds already infer ownership of objects, and 4-year-olds can discern ownership on the basis of investment of labor, refraining from taking resources accordingly ( Kanngiesser et al., 2020 ). In adolescence, the things an individual owns can be enveloped into his or her identity—creating an “extended self” ( Belk, 2018 ).…”
Section: Evolutionary Mismatchmentioning
confidence: 99%
“…Thus, humans tend to accumulate—and carry on their person—significant amounts of stuff, in addition to caching things they “own” (Figure 1). Supporting this assertion is the tendency of human children, unlike great apes, to respect ownership, 35 though the development of ownership concepts differs between cultures 36 . Today, mobile containers are used to retain and transport surpluses of food and water for future consumption or for later sharing with others, as well as to carry phones, money, keys, pens, contraceptives, cosmetics, and numerous other tools.…”
Section: Containers In the Ethnographic Presentmentioning
confidence: 99%